2011
DOI: 10.1159/000329999
|View full text |Cite
|
Sign up to set email alerts
|

Role of p53 in Neurodegenerative Diseases

Abstract: Background: p53 plays an important role in many areas of cellular physiology and biology, ranging from cellular development and differentiation to cell cycle arrest and apoptosis. Many of its functions are attributed to its role in assuring proper cellular division. However, since the establishment of its role in cell cycle arrest, damage repair, and apoptosis (thus also establishing its importance in cancer development), numerous reports have demonstrated additional functions of p53 in various cells. In parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
86
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(93 citation statements)
references
References 360 publications
(177 reference statements)
6
86
0
1
Order By: Relevance
“…Several studies have attributed p53-mediated apoptosis to a number of acute and chronic neurodegenerative disorders, including excitotoxicity, AD, Parkinson disease, multiple sclerosis, and Huntington disease (3). Accumulating evidence supports the role of reactive oxygen species in prompting DNA damage in neurodegenerative disease (4), leading to p53-dependent apoptosis.…”
mentioning
confidence: 99%
“…Several studies have attributed p53-mediated apoptosis to a number of acute and chronic neurodegenerative disorders, including excitotoxicity, AD, Parkinson disease, multiple sclerosis, and Huntington disease (3). Accumulating evidence supports the role of reactive oxygen species in prompting DNA damage in neurodegenerative disease (4), leading to p53-dependent apoptosis.…”
mentioning
confidence: 99%
“…For example, p53 was found to be highly elevated in brains affected by several neurodegenerative diseases, including Alzheimer’s disease (AD), Parkinson’s disease (PD), Huntington’s disease (HD), amyotrophic lateral sclerosis (ALS), HIV-associated neurocognitive disorders (HAND), etc. [59]. Furthermore, several epidemiological studies have found an inverse correlation between the risk of developing neurodegenerative disorders and cancer [6062], suggesting that some common protein effectors might likely be involved between these two multifactorial chronic pathologies.…”
Section: Discussionmentioning
confidence: 99%
“…This protein confers its tumor suppressive activities predominantly by acting as a transcription factor, transactivating over two hundred different target genes. p53 has also been found to be a critical factor governing innate and adaptive immune responses, reproduction, development, neural degeneration and aging (Chang et al, 2012; Danilova et al, 2008; Levine et al, 2011; Menendez et al, 2013; Poyurovsky and Prives, 2010). More recently, the relationship between p53 and metabolism has become the focus of new studies, particularly with the revelation that the role of p53 in metabolism may be essential to its tumor suppressor function (Li et al, 2012; Long et al, 2013; Maddocks et al, 2013; Vousden and Ryan, 2009).…”
Section: Introductionmentioning
confidence: 99%